Fedbatch operation using Clostridium acetobutylicum suspension culture as biocatalyst for enhancing hydrogen production - Chin, H. L.; Chen, Z. S.; Chou, C. P. (Biotechnology Progress, 2003)
We demonstrated the feasibility of fedbatch operation using Clostridium acetobutylicum suspension culture as a biocatalyst for the continuous production of hydrogen. The optimum operating pH and temperature of the current cultivation system for hydrogen production were pH 6.0 and 37degreesC, respectively. The volumetric loading of the bioreactor for hydrogen production can be as high as 650 mmol hydrogen/L culture with a yield at approximately 2.0 mol hydrogen/mol glucose. Acetate and butyrate made up approximately 80% of the total metabolites. The inhibitory effect from the two metabolites on the hydrogen production process was investigated. Butyrate at a concentration higher than 13 g/L significantly inhibited not only cell growth but also hydrogen production (i.e., specific hydrogen production rate). Acetate appears to be less toxic than butyrate to the hydrogen production process. While significantly inhibiting cell growth, acetate hardly affected hydrogen production. Finally, the factors limiting cultivation performance were discussed and possible strategies for enhancing the production of hydrogen were proposed.